Determining production level under uncertainty using fuzzy simulation and bootstrap technique, a case study - Mohammadreza Hamidi; Kamran Shahanaghi; Armin Jabbarzadeh; Ehsan Jahani; Zahra Pousti (Journal of Industrial Engineering International, 2017)
In every production plant, it is necessary to have an estimation of production level. Sometimes there are many parameters affective in this estimation. In this paper, it tried to find an appropriate estimation of production level for an industrial factory called Barez in an uncertain environment. We have considered a part of production line, which has different production time for different kind of products, which means both environmental and system uncertainty. To solve the problem we have simulated the line and because of the uncertainty in the times, fuzzy simulation is considered. Required fuzzy numbers are estimated by the use of bootstrap technique. The results are used in production planning process by factory experts and have had satisfying consequences. Opinions of these experts about the efficiency of using this methodology, has been attached.
Keywords: 650; Production planning; Fuzzy simulation; Bootstrap technique; Discrete event simulation